PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA PENYELUDUPAN MANUSIA - Mhd. Teguh Syuhada Lubis (Universitas Muhammadiyah Sumatera Utara, 2017)
The developments of information technology and transport is increasing so as to make the boundaries between countries increasingly apparent. Traffic is more easily accessible. More open the traffic between countries in the globalization era also led the increasing of mobility of goods and people between one country to another country. The opening track between countries are not only used for business necessities of life, but also the movement of people from one country to another. The flow of human movement, basically is the goal to find the solution of all the problems that they find in the place of themselves. The movement of human movement is a gap for the occurrence of crime. In the context of transnational crime, human trafficking is a form of transnational organized crime that potentially cause the kinds of implications for other crimes. Human smuggling can be a weak dose of a country’s legal system in dealing with covert motivation of the imigiran to make the country as a state intermediary for the crime. Other crimes may arise due to the omission of the practice of human trafficking, such as conventional crimes (fraud, rape, murder, and theft), shipping, human trafficking, money laundering, banking crimes and terrorism.